Beeline to murder - Lester, Meera (Lester, Meera. Henny Penny Farmette mystery., 2015)
After an injury forced her to leave the police department, Abigail Mackenzie started a second career as a farmer. Raising chickens, harvesting honey from her bee colony, and growing heirloom vegetables on her farmette in the beautiful Bay Area town of Las Flores, Abby has embraced all the benefits of a peaceful life. But when she attempts to deliver her trademark honey to local pastry chef Jean-Louis Bonheur and finds him dead in his shop, her old investigative instincts kick in. After the coroner rules the death a suicide, the chef's handsome French-Canadian brother insists on hiring Abby to find out who really killed Jean-Louis.